Designing mLearning : tapping into the mobile revolution for organizational performance - Quinn, Clark N., 1956- (San Francisco : Pfeiffer, 2011)
'This book presents principles for designing and implementing mobile learning solutions. Based upon previous mobile writing and thinking, this invaluable resource captures the resulting integrated approach and provides guidance for mobile learning regardless of device. The book debunks the myths, defines the opportunity, presents examples, provides guiding principles, structures the design process, presents implementation considerations, and places mobile learning in the overall strategic picture. It is intended to be the definitive work on mobile learning design.'--
Includes bibliographical references and index.
Keywords: Management -- Communication systems; Mobile communication systems; Organizational learning; Organizational effectiveness; Information technology -- Management; Employees -- Training of -- Computer-assisted instruction; BUSINESS & ECONOMICS / Training